Comparative fire behavior of reinforced RPC and NSC simply supported beams. (15th April 2019) - Hou, Xiaomeng; Ren, Pengfei; Rong, Qin; Zheng, Wenzhong; Zhan, Yao
Highlights: Fire resistance of four RPC beams exposed to fire was conducted. Under-reinforced RPC beams may fail as lightly reinforced beams in fire. The use of hybrid fibers is effective to prevent fire-induced spalling of RPC beams. Given same flexural capacity, RPC beams have lower fire resistance than NSC beams. Insulations are required for improving the fire resistance of RPC beams. Abstract: The behavior of reactive powder concrete (RPC) at high temperatures has been mainly studied at the material level, and relatively few experimental studies have been conducted on the fire performance of RPC beams. An experimental investigation was therefore undertaken to explore the behavior of four reinforced RPC simply supported beams exposed to fire on three sides. The results such as cross-section temperatures at different heights, mid-span deflections, axial thermal expansion, crack patterns, failure modes, and fire resistance of beams are presented in this paper. The data obtained from the tests were also used to evaluate the effects of significant parameters such as RPC cover thickness, load level and fiber content, on the thermal and structural response of RPC beams. The results show that during fire, RPC beams that are under-reinforced at room temperature may fail as the lightly reinforced beams. Both RPC cover thickness and load level significantly affect the fire behavior of reinforced RPC simply supported beams. The addition of 2% steel fibers and 0.2% polypropylene fibers is an effective method to prevent the fire induced spalling of the reinforced RPC beams. Furthermore, based on the experimental studies on RPC beams and the numerical studies on RPC beams and normal strength concrete (NSC) beams, the difference in the fire resistance performance between RPC beams and NSC beams was investigated. It is shown that under the same flexural capacity at room temperature, the NSC beams exhibit a better fire resistance performance than the RPC beams.